3(x-5)+4=2(3x-1)

Simple and best practice solution for 3(x-5)+4=2(3x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-5)+4=2(3x-1) equation:



3(x-5)+4=2(3x-1)
We move all terms to the left:
3(x-5)+4-(2(3x-1))=0
We multiply parentheses
3x-(2(3x-1))-15+4=0
We calculate terms in parentheses: -(2(3x-1)), so:
2(3x-1)
We multiply parentheses
6x-2
Back to the equation:
-(6x-2)
We add all the numbers together, and all the variables
3x-(6x-2)-11=0
We get rid of parentheses
3x-6x+2-11=0
We add all the numbers together, and all the variables
-3x-9=0
We move all terms containing x to the left, all other terms to the right
-3x=9
x=9/-3
x=-3

See similar equations:

| 3y^2+109y-616=0 | | x(2x-1)=3x+6 | | 27x3=351 | | Y^2-31y=0 | | -1-4n-3=17+3n | | 24+2n=48 | | 30=5w+20 | | 25=15+10g | | 3^x-2^x-65=0 | | 3y+6=52 | | r+1=28/4 | | 20+5c(c-2)=10c | | n2+3=1 | | 2c-2=30 | | 400=4a^2 | | m3+4=1 | | 121x^2=9 | | 18+x+37=90 | | x-4x=14 | | 1/4+y=2/4 | | 13=2^2^n-7^1^n+5 | | 13=2^2n-7^1n+5 | | 17+k=88 | | 5x^2+7.5x-37.5=0 | | 12^(2x)=417 | | X2-7x-9=0 | | 5(x-4)+7=5x+13 | | 0.03^x*38=500 | | 8+(5+2x)=20-(4-x) | | 2x+15=5x-15 | | 28x=178 | | 4+4x4=20 |

Equations solver categories